THE ROLE OF DNA-METHYLTRANSFERASES IN THE LIFE CYCLE OF HEPATITIS B VIRUS AND PATHOGENESIS OF CHRONIC HEPATITIS B - D. S. Kostyushev; A. P. Zueva; S. A. Brezgin; A. D. Lipatnikov; E. V. Volchkova; V. V. Maleyev; V. P. Chulanov (Вопросы вирусологии, 2018)
Chronic hepatitis B is caused by a persistent form of hepatitis B virus, covalently closed circular DNA (cccDNA). Stability of cccDNA is associated with intracellular localization of cccDNA and formation of minichromosome, regulated by epigenetic mechanisms. One of the key mechanisms in epigenetics is methylation of DNA on CpG islands. Expression levels of DNA-methyltransferases (DNMTs) in chronic hepatitis B patients were shown to be upregulated. Nevertheless, the role of DNMTs in the life cycle of HBV and their effects on the cell remain elusive. In this review, we discuss latest achievements on the role of DNMTs in chronic hepatitis B and HBV in vitro models.